Multimodal information density is highest in question beginnings, and early entropy is associated with fewer but longer visual signals. - Trujillo, James P.; Holler, Judith (Discourse Processes)
When engaged in spoken conversation, speakers convey meaning using both speech and visual signals, such as facial expressions and manual gestures. An important question is how information is distributed in utterances during face-to-face interaction when information from visual signals is also present. In a corpus of casual Dutch face-to-face conversations, we focus on spoken questions in particular because they occur frequently, thus constituting core building blocks of conversation. We quantified information density (i.e. lexical entropy and surprisal) and the number and relative duration of facial and manual signals. We tested whether lexical information density or the number of visual signals differed between the first and last halves of questions, as well as whether the number of visual signals occurring in the less-predictable portion of a question was associated with the lexical information density of the same portion of the question in a systematic manner. We found that information density, as well as number of visual signals, were higher in the first half of questions, and specifically lexical entropy was associated with fewer, but longer visual signals. The multimodal front-loading of questions and the complementary distribution of visual signals and high entropy words in Dutch casual face-to-face conversations may have implications for the parallel processes of utterance comprehension and response planning during turn-taking.